2018
DOI: 10.1007/s00414-018-1809-5
|View full text |Cite
|
Sign up to set email alerts
|

Cranial secular change from the nineteenth to the twentieth century in modern German individuals compared to modern Euro-American individuals

Abstract: Studying secular changes on human skulls is a central issue in anthropological research, which is however insufficiently investigated for modern German populations. With our study, we focus on morphological cranial variations within Germans during the nineteenth and twentieth centuries. To study this, we recorded different facial landmarks from a cohort study of about 540 German individuals of different age and sex by calculating their cranial size, shape dimensions, and cranial module and cranial capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These differences may be caused by the geographical regions, descent, genetic profile, and even different sample sizes of the different studies. 14,15 This finding provide data for establishing the reference value of normal Chinese adult cranial capacity.…”
mentioning
confidence: 60%
“…These differences may be caused by the geographical regions, descent, genetic profile, and even different sample sizes of the different studies. 14,15 This finding provide data for establishing the reference value of normal Chinese adult cranial capacity.…”
mentioning
confidence: 60%
“…Research across the world has shown that over time, various skeletal dimensions have undergone significant changes (Langley & Jantz, 2020). For example, the cranium has been found to turn increasingly long, high, and narrow, with a longer cranial base from the 19th to the mid-20th century in a comparative study between Germans and Euro-Americans (Jellinghaus et al, 2018). Similarly, studies focused exclusively on North American cranial morphological changes from the mid-19th century to the 1970s found an elongation and narrowing of the cranial vault, as well as an increase in its height.…”
Section: Model Accuracy Values From the Sexest Software Using The How...mentioning
confidence: 99%